DETERMINAN KEPUTUSAN PETANI TERHADAP PENJUALAN LADA PUTIH DI KECAMATAN AIR GEGAS KABUPATEN BANGKA SELATAN - Annisa Pradnya Paramitha; Yudi Sapta Pranoto; Rati Purwasih (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2021)
White pepper is commodity of agriculture sector in Province of Bangka Belitung Island which it has been cultivated from generation to generation by society as the source of income supporting the economy. White pepper farming income is obtained from sales which it requires the farmers to make decisions in the form of direct selling or delay selling. This research aim to: 1) Analyzing the contribution of white pepper farming income as the foundation of farmer’s economy and 2) Analyzing the determinant of farmer’s decision on white pepper sales. This research was conducted in Delas Village, Nyelanding Village, and Air Gegas Village, Air Gegas Sub-district on September 2020 until July 2021. The research method used is survey. The sampling method used is quota sampling with the sample amount 60 people whos divided into 2 categories, namely 30 people for the farmer whos direct selling and 30 people for the farmer whos delay selling. The data collection methods used are observation, interview, questionnaire, and documentary study. The data analysis method used are quantitative descriptive analysis and regression logistic binary analysis. The research result shows that 1) The contribution of white pepper farming income is 5,89 percent on total income to supply the necessities of life amount Rp. 30.418.500 per year and 2) The determinant of farmer’s decision on white pepper sales are age, farming experience, espousal in agricultural institution, and availability of agricultural product processing industry with the value of r square amount 0,728.